ANALISIS POSTUR PEKERJA PADA CV AGUS INSAN JAYAMENGGUNAKAN PENDEKATAN ERGONOMI - Titis Sulistiyo Wahyuning Asih (2021)
CV Agus Insan Jaya is a printing industry whose main activity is to make sheets of paper to be used as envelopes. The main focus of this company is in the field of paper gluing or finishing. Almost all activities in this company are still done manually using human power. These activities are paper gluing and packaging. Only paper printing activities have used a paper cutting machine or commonly called a pound machine. In the process of packaging the worker's body posture is in a position that is not good, so it can cause the risk of injury if it is done continuously. The method used in this research is Nordic Body Map (NBM) , Quick Exposure Check (QEC ), andJob Strain Index (JSI) to reduce the level of pain complaints felt by workers. The results of data processing using the QEC and JSI methods showed that workers at the packaging work station had a high level of risk, with the results of the NBM questionnaire the three workers experienced complaints of pain in the neck and waist. The proposed improvement is to design a tool based on anthropometric calculations in the form of a table for packaging workers. The results of the comparison between NBM, QEC and JSI , when before and after repairs were made, showed that workers' complaints and risk levels decreased. The results of the NBM questionnaire showed that the neck and waist had decreased to be quite painful. And the results of the QEC and JSI methods show that workers at the packaging work station have a moderate level of risk.